ナンキョク ニ オケル ウチュウ ブッシツ ニ カンスル ケンキュウ 1 - 島, 誠; シマ, マコト; 矢吹, 英雄; ヤブキ, ヒデオ; SHIMA, Makoto; YABUKI, Hideo (国立極地研究所, 1968)
P(論文) The study of the extraterrestrial material collected in Antarctica is reported. The extrateirestnal material comprises cosmic dust, tektite, and meteorite. Antarctica is the most suitable place for collecting such material, since the Antarctic Continent is covered with thick ice and is hardly contaminated by terrestrial material, so that the extrater-restrial material is easily picked up. This report describes the chemical composition and the size distribution of cosmic dust. By the chemical composition, cosmic dust is classified into three groups, 1) Ni-Fe group, 2) Fe group and 3) silicate group. The glassy material composed mainly of silica is thought to be a kind of tektite. Annual fall rate of cosmic dust near Syowa Station would be estimated at 3 × 10^4 ton/year. departmental bulletin paper